Cryptic species, life cycles, and the phylogeny of Clytia (Cnidaria: Hydrozoa: Campanulariidae) - Lindner, Alberto; Govindarajan, Annette F.; Migotto, Alvaro E. (Zootaxa, 2011)
Medusae and polyps of Clytia are abundantly found in coastal marine environments and one species in the genus—Clytia hemisphaerica (Linnaeus, 1767)—has become an important experimental model. Yet, only 10 species in the genus have had their life cycle investigated. Most species of Clytia are also poorly described, and detailed life cycle and morphological studies are needed for accurate species-level identifications. Here, we investigated the life cycle of Clytia elsaeoswaldae Stechow, 1914, a species described for the tropical western Atlantic and subsequently considered conspecific to the nearly-cosmopolitan species Clytia gracilis (Sars, 1850) and Clytia hemisphaerica, originally described for the temperate North Atlantic. Based on observations of mature medusae and multiple colonies from southeastern Brazil and the U. S. Virgin Islands (type locality), our results show that C. elsaeoswaldae is morphologically distinct from C. gracilis and C. hemisphaerica. The morphological results are corroborated by a multigene phylogenetic analysis of the genus Clytia, which shows that C. gracilis-like species form a polyphyletic group of several species. These results suggest that the nearly-cosmopolitan distribution attributed to some species of Clytia may be due to the non-recognition of morphologically similar species with more restricted ranges.